2017
DOI: 10.1016/j.foodchem.2017.05.129
|View full text |Cite
|
Sign up to set email alerts
|

Epoxyalkenal-trapping ability of phenolic compounds

Abstract: Lipid oxidation products have been shown to produce changes in food quality and safety as a consequence of carbonyl-amine reactions. Some of these reactions can be prevented by the use of phenolics, although the lipid-derived carbonyl trapping ability of phenolics is still poorly understood. In an attempt to fill this gap, the reactions of 4,5-epoxy-2-hexenal, 4,5-epoxy-2-heptenal, and 4,5-epoxy-2-decenal, with 2-methylresorcinol and 2,5-dimethylresorcinol were studied. These reactions produced diverse 1,3a,4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Thus, adducts were produced to a small extent at neutral pH, but their yields increased rapidly to higher pH values. This behavior is likely related to the increase of nucleophilicity of phenolic carbons, also observed in the reaction of phenolics with other aldehydes (Zamora et al, 2017). This high nucleophilicity is needed for the first step of the reaction pathway proposed in Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, adducts were produced to a small extent at neutral pH, but their yields increased rapidly to higher pH values. This behavior is likely related to the increase of nucleophilicity of phenolic carbons, also observed in the reaction of phenolics with other aldehydes (Zamora et al, 2017). This high nucleophilicity is needed for the first step of the reaction pathway proposed in Fig.…”
Section: Discussionmentioning
confidence: 71%
“…In nature, polyphenols occur as monomers, oligomers, and polymers (proanthocyanidins, condensed tannins). There is also evidence indicating that, during the storage and aging of food products and beverages with a high content of flavonoids, the latter react with carbonyl compounds such as acetaldehyde, methylglyoxal, glyoxylic acid, and furfurol, which results in the formation of monomeric, oligomeric, and polymeric adducts [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…26 As an exception, in 4,5-epoxy-2alkenals, the reaction is initiated by the attack of the hydroxyl group of the phenolic to the epoxide ring of the lipid carbonyl because of the high reactivity of this three membered ring. 27 4-Hydroxy-2-alkenals are basically ,-unsaturated carbonyl compounds. Therefore, its behavior, at least at the initial steps, should be similar to other unsaturated carbonyl compounds.…”
Section: Discussionmentioning
confidence: 99%
“…18 In addition, formation of these carbonyl-phenol adducts has been related to the protective function of some phenolics on the formation of heterocyclic aromatic amines and biogenic amines by carbonylamine reactions, 19,20 and the beneficial properties of polyphenolic-rich foods such as tea or coffee. 21 Although carbonyl-phenol reactions with different lipid-derived reactive carbonyls have been described, [22][23][24][25][26][27] the ability of phenolic compounds to trap and produce carbonyl-phenol adducts with 4-hydroxyalkenals has not been described. To the best of our knowledge, although several studies have shown that 4-hydroxy-2-nonenal (HNE) seems to be effectively trapped by phenolics, 28,29 neither the produced reaction has been described in detail nor the structure(s) of the formed adduct(s) has been unequivocally characterized.…”
Section: Introductionmentioning
confidence: 99%